Program rewitalizacji zlewni rzeki Cybiny oraz rekultywacji jeziora Swarzędzkiego = Revitalisation programme of Cybina river catchment and Swarzędzkie lake reclamation - Rychła, Anna; Gołdyn, Ryszard; Spieker, Jurgen; Eydeler, Inga; Becker, Michael; Hammerling, Ronny; Nixdorf, Brigitte (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Marked nontamination of the Cybina River is one of reasons of hipertrophy and degradation of the Swarzędzkie Lake. Situation of this lake in the lower course of the Cybina River resulted in high loading of nutrients and organic compounds. This pollution, originated from all over the catchment area is brought to the lake with water of main tributary.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)